The roles of familial transmission and smoking during pregnancy on executive function skills: A sibling-comparison study. (30th December 2022) - Knopik, Valerie S.; Micalizzi, Lauren; Marceau, Kristine; Loviska, Amy M.; Yu, Li; Bien, Alexandra; Rolan, Emily; Evans, Allison S.; Palmer, Rohan H. C.; Heath, Andrew C.
Abstract: This research examines maternal smoking during pregnancy and risk for poorer executive function in siblings discordant for exposure. Data ( N = 173 families) were drawn from the Missouri Mothers and Their Children study, a sample, identified using birth records (years 1998–2005), in which mothers changed smoking behavior between two pregnancies (Child 1 [older sibling]: M age = 12.99; Child 2 [younger sibling]: M age = 10.19). A sibling comparison approach was used, providing a robust test for the association between maternal smoking during pregnancy and different aspects of executive function in early-mid adolescence. Results suggested within-family (i.e., potentially causal) associations between maternal smoking during pregnancy and one working memory task (visual working memory) and one response inhibition task (color-word interference), with increased exposure associated with decreased performance. Maternal smoking during pregnancy was not associated with stop-signal reaction time, cognitive flexibility/set-shifting, or auditory working memory. Initial within-family associations between maternal smoking during pregnancy and visual working memory as well as color-word interference were fully attenuated in a model including child and familial covariates. These findings indicate that exposure to maternal smoking during pregnancy may be associated with poorer performance on some, but not all skills assessed; however, familial transmission of risk for low executive function appears more important.